Functions of Rho family of small GTPases and Rho-associated coiled-coil kinases in bone cells during differentiation and mineralization - Strzelecka-Kiliszek, Agnieszka; Mebarek, Saida; Roszkowska, Monika; Buchet, René; Magne, David; Pikula, Slawomir (Biochimica et biophysica acta. General subjects, 2017)
Members of Rho-associated coiled-coil kinases (ROCKs) are effectors of Rho family of small GTPases. ROCKs have multiple functions that include regulation of cellular contraction and polarity, adhesion, motility, proliferation, apoptosis, differentiation, maturation and remodeling of the extracellular matrix (ECM). Here, we focus on the action of RhoA and RhoA effectors, ROCK1 and ROCK2, in cells related to tissue mineralization: mesenchymal stem cells, chondrocytes, preosteoblasts, osteoblasts, osteocytes, lining cells and osteoclasts. The activation of the RhoA/ROCK pathway promotes stress fiber formation and reduces chondrocyte and osteogenic differentiations, in contrast to that in mesenchymal stem cells which stimulated the osteogenic and the chondrogenic differentiation. The effects of Rac1 and Cdc42 in promoting chondrocyte hypertrophy and of Rac1, Rac2 and Cdc42 in osteoclast are discussed. In addition, members of the Rho family of GTPases such Rac1, Rac2, Rac3 and Cdc42, acting upstream of ROCK and/or other protein effectors, may compensate the actions of RhoA, affecting directly or indirectly the actions of ROCKs as well as other protein effectors. ROCK activity can trigger cartilage degradation and affect bone formation, therefore these kinases may represent a possible therapeutic target to treat osteoarthritis and osseous diseases. Inhibition of Rho/ROCK activity in chondrocytes prevents cartilage degradation, stimulate mineralization of osteoblasts and facilitate bone formation around implanted metals. Treatment with osteoprotegerin results in a significant decrease in the expression of Rho GTPases, ROCK1 and ROCK2, reducing bone resorption. Inhibition of ROCK signaling increases osteoblast differentiation in a topography-dependent manner. [Display omitted] •Structure, expression, and functions of ROCK kinases (the effectors of RhoA GTPases), during bone formation and osseous diseases are reviewed.•RhoA/ROCK pathway in mesenchymal stem cells induces osteogenic and chondrogenic differentiations.•RhoA/ROCK pathway in chondrocytes represses chondrogenic genes; its inhibition prevents cartilage degradation and maintains cell phenotype.•RhoA/ROCK pathway regulates the mechanosensitivity of osteoblasts by stress fiber formation; its inhibition induces bone formation.•RhoE/ROCK/Cofilin pathway promotes podosome dynamics, osteoclast migration, sealing zone formation and, ultimately, bone resorption.